Solutions by everydaycalculation.com

How to solve 3x - 6 = x + 2? Get the answer and stepwise instruction to solve linear equation in one one variable 𝒙.

We have 3**x** - 6 = **x** + 2

First, we move the * x* terms to the LHS and constant terms to the RHS of the equation, inverting the sign on the terms. This is also called transposing method.

Transposition is a faster method and combines the following two steps, were we to solve the equation by:

i) Adding 6 to both sides

ii) Subtracting **x** from both sides

Therefore, 3**x** - **x** = 2 + 6

or, 2**x** = 8

Next, divide both sides by 2, which is the coefficent of **x**

2**x**2 = 82

**x** = 82

To simplify, divide both numerator and denominator by 2, which is the GCF of 8 and 2:

**x** = 41 or, **x** = 4

© everydaycalculation.com